2006
DOI: 10.1007/s00192-006-0096-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of incontinence in women with benign joint hypermobility syndrome

Abstract: The objective of this study was to determine whether the prevalence of urinary and anal incontinence in women with benign joint hypermobility syndrome (BJHS) was more than in a control group without this condition. The International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) and the Manchester Health Questionnaire were sent to 30 patients with benign joint hypermobility syndrome and 30 healthy women without this condition and results were compared. It was found out that the prevalence of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
1
11
1
Order By: Relevance
“…The prevalence of incontinence ranges from 42 % to 60 % [10]. This has been confirmed by our study, albeit with a greater prevalence of 73 %.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The prevalence of incontinence ranges from 42 % to 60 % [10]. This has been confirmed by our study, albeit with a greater prevalence of 73 %.…”
Section: Discussionsupporting
confidence: 88%
“…A significant portion of women with BJHS felt their LUTS had a negative impact on QoL. This is contrary to the published data from Jha et al [10], which showed that despite a statistically significant proportion of women with UUI and anal incontinence, their impact on QoL was minimal. When considering the second domain (incontinence impact on QoL) of the KHQ in relation to those with UI, a significant portion felt that this affected them moderately to severely.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…4 and Jha et al . 5 found that urinary and faecal incontinence was significantly higher in people with the condition than controls. Uterine prolapse has also been correlated similarly, a finding in association with incontinence that has been found in related conditions such as Marfan's and umbrella Ehlers Danlos syndrome in general.…”
Section: Discussionmentioning
confidence: 88%
“…Since the initial report of an association between JHM and POP in 1982 , the relationship has been consistently replicated in various populations using either the clinical Beighton criteria or the validated five‐item Hakim questionnaire , which are broadly comparable . Several studies have also considered an association with SUI, but have had conflicting results (Table ) . Pathophysiologically JHM could also be related to urinary storage symptoms, as JHM syndrome involves various autonomic nervous system‐related symptoms, associated with adrenoceptor hyper‐responsiveness .…”
Section: Introductionmentioning
confidence: 99%